The Lucy Collective - Women Of History, Women Of Fiction - Franková, Anna (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Tato práce je prototypem uživatelsky editovatelného databázového webu The Lucy Collective – Women Of History. Tento web bude shromažďovat informace o historických ženách a odkazy na zdroje, a bude sloužit jako rozcestník pro učitele, tvůrce a další zájemce o toto téma. Hlavním cílem prototypu je předvést strukturu, způsob použití a vzhled webu, a sloužit jako podklad pro vznik výsledné verze.

This project is a prototype of a database-driven website with user-editable content The Lucy Collective – Women Of History. This site will collect information about historical women and links to sources related to them, and serve as a "first-step" resource for educators, creators, and other people interested in the topic. The prototype's main goal is to present the intended structure, useability, and design of the final website, and serve as a basis for building the final working version.
The Lucy Collective - Women Of History, Women Of Fiction
Keywords: webdesign; návrh webu; prototyp; grafický design; databáze; uživatelsky editovatelný web; wiki; historické ženy; ženy v médiích; feminismus; webdesign; prototype; demo; graphic design; database; user-editable content; wiki; historical women; women in history; women in media; feminism